Synthesizing Polyaniline With Laccase/O2 as Catalyst - Walde, Peter; Kashima, Keita; Ćirić-Marjanović, Gordana (Frontiers in Bioengineering and Biotechnology, 2019)
The polymerization of aniline to polyaniline (PANI) can be achieved chemically, electrochemically or enzymatically. In all cases, the products obtained are mixtures of molecules which are constituted by aniline units. Depending on the synthesis conditions there are variations (i) in the way the aniline molecules are connected, (ii) in the average number of aniline units per molecule, (iii) in the oxidation state, and (iv) in the degree of protonation. For many possible applications, the synthesis of electroconductive PANI with para-N-C-coupled aniline units in their half-oxidized and protonated state is of interest. This is the emeraldine salt form of PANI, abbreviated as PANI-ES. The enzymatic synthesis of PANI-ES is an environmentally friendly alternative to conventional chemical or electrochemical methods. Although many studies have been devoted to the in vitro synthesis of PANI-ES by using heme peroxidases with added hydrogen peroxide (H2O2) as the oxidant, the application of laccases is of particular interest since the oxidant for these multicopper enzymes is molecular oxygen (O2) from air, which is beneficial from environmental and economic points of view. In vivo, laccases participate in the synthesis and degradation of lignin. Various attempts of synthesizing PANI-ES with laccase/O2 in slightly acidic aqueous media from aniline or the linear aniline dimer PADPA (p-aminodiphenylamine) are summarized. Advances in the understanding of the positive effects of soft dynamic templates, as chemical structure guiding additives (anionic polyelectrolytes, micelles or vesicles), for obtaining PANI-ES-rich products are highlighted. Conceptually, some of these template effects appear to be related to the effect "dirigent proteins" exert in the biosynthesis of lignin. In both cases intermediate radicals are formed enzymatically which then must react in a controlled way in follow-up reactions for obtaining the desired products. These follow-up reactions are controlled to some extent by the templates or specific proteins.